Mortality in relation to the functional capacities of people with disabilities living at home. Issue 3 (September 1982) - Warren, M D; Knight, R
Abstract : The mortality experienced by a group of 1534 impaired people identified by means of a census-type survey of all households in the City of Canterbury is related to the degree of difficulty in carrying out selected self-care activities as reported by the impaired people. Although not entirely consistent, the findings in relation to people in their own homes agree with previously reported findings among patients in long-stay hospitals and residents in institutions that increasing difficulties in self-care (and therefore of dependency) are associated with increased mortality rates. These findings suggest that there is no clear boundary between some services for disabled people and those for terminal care, and that many severely handicapped people at home require co-ordinated and flexible care from nurses, social workers, and doctors.